ERROR ANALYSIS OF THE WRITTEN ENGLISH ESSAY AT THE THIRD SEMESTER OF ENGLISH DEPARTEMENT - Syarfuni (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
This study examiners error in a corpus 25 essay written by 25 participant. The participants are the third semester of who are studying at the English department; 4 male and 21 females. The have experienced approximately for one semester in subject writing. All participants are come form non-English education background and hardly communicate in English out the college. The instruments used for this study was participants’ written essay. All of error in the essays were identified and classified into various categorizations. The result of the study show that six common errors committed by the participants were singular/plural form, verb tense, word choice, preposition, subject-verb agreement and word order. These aspects of writing in English pose the most difficult problems to participants. This study has shed light on the manner in which students internalize the rules of the target language, which is English. Such an insight into language learning problems is useful to teachers because it provides information on common trouble-spots in language learning which can be used in the preparation of effective teaching materials.